2015
DOI: 10.1134/s0022093015020088
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin and neuropeptide FMRFamide in the nervous system of Opisthioglyphe ranae (Trematoda: Plagiorchiidae). An iimmunocytochemical study

Abstract: The presence and localization of the serotoninergic and FMRFamidergic structures in the nervous system of the trematode Opisthioglyphe ranae, the marsh frog intestinal parasite, was studied using immunocytochemistry. The serotonin-immunoreactive nerve cells and fibers were revealed in the head ganglia, circular commissure, longitudinal nerve cords and their connective commissures, as well as around the oral and ventral suckers, esophagus and genital pore. FMRFamide immunoreactivity was observed in the head gan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 18 publications
2
2
0
Order By: Relevance
“…The cephalic ganglia found around the prepharynx and pharynx area can be considered a 'true' brain, as it is the centre for the inhibiting and controlling reflexes in the peripheral nerve net (Halton & Gustafsson 1996). Our results are also in accordance with those found for other trematodes, like E. caproni, Opisthorchis viverrini and Opisthioglyphe ranae ( Sebelov a et al 2004;Leksomboon et al 2012;Terenina et al 2015). Although the ganglia were strongly stained, the anterior region of trematodes usually presents large commissures that compose the central nervous system of the parasite, but these commissures were only lightly stained in our work.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The cephalic ganglia found around the prepharynx and pharynx area can be considered a 'true' brain, as it is the centre for the inhibiting and controlling reflexes in the peripheral nerve net (Halton & Gustafsson 1996). Our results are also in accordance with those found for other trematodes, like E. caproni, Opisthorchis viverrini and Opisthioglyphe ranae ( Sebelov a et al 2004;Leksomboon et al 2012;Terenina et al 2015). Although the ganglia were strongly stained, the anterior region of trematodes usually presents large commissures that compose the central nervous system of the parasite, but these commissures were only lightly stained in our work.…”
Section: Discussionsupporting
confidence: 89%
“…The tegumental pattern of both adults and metacercariae of P. macrostomum follows the architecture of the characteristic digenean tegument (Smyth & Halton 1983;Threadgold 1984). The diagonal, circular and longitudinal muscle fibres, easily visible by confocal images in this work, have also been found in other digenean parasites (Mair et al 2000;Sebelov a et al 2004;Santos et al 2013;Terenina et al 2015).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…In D. dendriticum, radial, circular, and longitudinal muscles were found in the pharynx, diagonal and longitudinal muscles were observed in the wall of the esophagus, and circular, longitudinal, and diagonal muscles were detected in the anterior region of the intestine. Previous studies identified the presence of circular, longitudinal, and radial fibers in the pharynx; circular and longitudinal fibers, and in some cases diagonal fibers, were found in the esophagus and intestine of some trematodes (Mair, Maule, Shaw, Johnston, & Halton, 1998;Nefedova et al, 2021;Terenina et al, 2015;Tolstenkov et al, 2007Tolstenkov et al, , 2010. It should be noted that the musculature of the digestive system in trematodes has not yet been sufficiently studied and requires further careful investigation.…”
mentioning
confidence: 97%